Coronary circulatory indices in non-infarct related vascular territories in a porcine acute myocardial infarction model. (25th November 2020) - Lee, S.H; Kim, H.K; Lee, J.M; Hong, Y.J; Choi, K.H; Shin, E.S; Nam, C.W; Doh, J.H; Yang, J.H; Song, Y.B; Hahn, J.Y; Choi, S.H; et al.
Abstract: Background: There has been debate on the reliability of fractional flow reserve (FFR) or resting pressure-derived indices in non-IRA of patients with acute ST-segment elevation myocardial infarction. Purpose: This study aimed to evaluate temporal changes of coronary hemodynamic and physiologic indices in non-infarct related artery (non-IRA), which might be affected by adjacent infarcted myocardium, using an experimental animal model of acute myocardial infarction (AMI). Methods: In Yorkshire swine, acute myocardial infarction was simulated with selective balloon occlusion at left circumflex artery (LCX) as IRA for 30 minutes. Non-IRA stenosis was created using bare metal stent implantation in left anterior descending artery (LAD) 4 weeks before the experiments. Serial changes of systemic hemodynamics, coronary pressure, and Doppler-derived coronary flow velocity were measured in a non-occluded LAD as non-IRA from baseline, balloon occlusion of LCX, and 15 minutes after reperfusion of LCX. Results: Among the 6 experimental subjects, the median diameter stenosis of non-IRA was 33.9% (Q1-Q3: 21.7%-46.1%). During balloon occlusion of IRA, there were transient significant changes in both resting and hyperemic aortic pressure (Pa), distal coronary pressure (Pd), averaged peak velocity (APV), trans-stenotic pressure gradient (PG), and microvascular resistance of non-IRA (all P values<0.020). After reperfusion of IRA, the resting APV (P=0.002) and resting trans-stenotic PG (P=0.004) were significantly increased and resting microvascular resistance (P=0.004) was significantly decreased than those in baseline phase. However, the hyperemic APV (P=0.479), hyperemic trans-stenotic PG (P=0.778), and hyperemic microvascular resistance (P=0.816) were not significantly different compared with those in the baseline phase. After reperfusion, the FFR in non-IRA was not significantly different (0.94±0.01 vs. 0.93±0.01, P=0.353), while the CFR (1.93±0.07 vs. 1.36±0.07, P=0.025) and resting Pd/Pa (0.98±0.01 vs. 0.94±0.01, P=0.017) were significantly lower than baseline values. Conclusions: In a porcine AMI model, occlusion of IRA induced significant changes of systemic hemodynamics and coronary circulatory indices of non-IRA. However, after reperfusion of IRA, FFR did not change significantly, while resting Funding Acknowledgement: Type of funding source: Other. Main funding source(s): 1. Philips/Volcano, 2. Bio & Medical Technology Development Program of the National Research Foundation of the Korean government